Agricultural change and farmworker living standards in post-apartheid South Africa - Le Roux, Leonard (School of Economics, 2020)
Commercial agriculture in South Africa has been subject to accelerated regulatory and economic change in the time since the country’s democratization. This dissertation focusses on some of the interactions of these changes with the prospects of low-income farmworkers and farm dwellers through exploring two interlinked questions. The first of these asks whether consolidation in the industry has extended to growing firm size and in-turn, whether farmworkers in larger firms earn higher wages than those in small firms. An analysis of the firm-size earnings relationship using long run labour survey data is discussed in the context of current debates on agrarian policy. The second question relates to the process of rural-urban migration off commercial farms and into urban areas in the post-apartheid period. Using a panel of individuals and in so doing, controlling for unobserved individual heterogeneity and initial household fixed effects, a difference in differences approach is used to estimate the impacts of migration on various measures of individual living standards. Together these two questions attempt to characterise aspects of the changing nature of life on farms. The results suggest that there exists a significant firm-size earnings premium for farmworkers and that this may be increasing over time. In addition the National Income Dynamics Study (NIDS) data suggests that migration off farms has mixed implications for living standards, but is associated with significant gains in per-capita income, electricity and sanitation access.